Analysis of Cross-border Mergers and Acquisitions Activities in the Chinese automobile industry: The case of Company X and Company Y - Wang, Ke (2017)
Within the developing of globalization, cross-border M&A is deemed as an effective strategy to achieve internationalization. As the world’s largest emerging country, China has experienced rapid economic growth and increasingly participated in foreign investments. The Chinese automobile industry occupies a significant status in Chinese foreign investment. This dissertation targets to conduct research on motivation theory of cross-border M&A and potential problems in the integration process by analyzing the case of Chinese Company X’s acquisition of Swedish Company Y.